Uncovering factors influencing consumers’ interest for craft beer: A study on microbreweries in Bangalore, India. - Ass. Prof. Dr. Vidya Patwardhan; Ass. Prof. Paritosh Dabral; Ms. Jyothi Mallya (African Journal of Hospitality, Tourism and Leisure, 2019)
The rapid emergence of demand for premium craft beer owing to changing cultural attitudes of young and affluent population contributed to the positive growth outlook for beer market in India. Bangalore, a cosmopolitan and progressive city, now considered as a favorite destination for Indians and expatriates has earned itself the title of “The Pub capital of India”. Being recognized as a “tech hub with a taste for fun” the city has been greatly affected by the western phenomenon of craft beer renaissance. Hence, with an objective to understand the factors that influence brand loyalty towards microbreweries was considered suitable to partake in this research study. The attributes such as brand image, purchase criteria, product attribute, brewery attribute, and customer satisfaction was considered to test brand loyalty of commercial craft beer consumers. Based on the data collected from 358 consumers visiting microbreweries, the regression analysis indicated that brand image and purchase criteria have a significant relationship with brand loyalty. Additionally respondents provided novel suggestions that can help businesspersons in the craft beer division to appreciate the consumption style to meet the preferences and desires of customers. These outcomes are significant to understand the consumers’ actions in the craft beer market to produce and market the best possible and widely accepted product in an ever emerging micro-brewing sector in India.